More of the Same? D’Holbach and the Temptation of Self-Quotation - Ruggero Sciuto (Modern Languages Open)
In his ‘Voltaire autoplagiaire’, Nicholas Cronk looks at Voltaire’s tendency to self-quote (either openly or more stealthily) and argues that, while in the eighteenth century classical and Renaissance attitudes towards repetitions were already starting to be questioned, the patriarche de Ferney turned self-plagiarism into something of a stylistic signature, putting forward a ‘véritable esthétique du “copier/coller”’. The present contribution looks at the works of eighteenth-century atheist and determinist philosopher Paul Thiry d’Holbach, which were commonly dismissed by his contemporaries as tedious, repetitious and stylistically flat, to examine his attitudes towards self-quotation. Rudolf Besthorn and Alain Sandrier have already drawn attention to several phrases and constructions that are typical of d’Holbach’s style, and which appear almost obsessively in his works. They correctly suggested that, far from being the marks of an inattentive or poor writer, these syntagmata fit perfectly within the baron’s argumentative prose and serve very well his proselytising strategy. As I shall argue in this essay, however, d’Holbach’s somewhat formulaic prose and tendency to repeat himself are counterbalanced by a parallel striving for varietas: while repeating his ideas time and again within each work and across his textual corpus, d’Holbach is careful never to self-quote verbatim and always to find a perfect balance between same and new, as it were. Politically and philosophically an extremely radical author, d’Holbach took all possible measures to conceal his authorship of his texts, publishing them all either anonymously or pseudonymously. Very few people in the eighteenth century knew about his authorship of his works, and even today the contours of his textual corpus are regrettably indistinct. Could d’Holbach’s repetitious and yet chameleonic style, this ‘aesthetic of the hidden self-quotation’, as I shall dub it, be an attempt on d’Holbach’s part to help his readers (or posterity) reconstruct his dismembered textual corpus?